2016
DOI: 10.1021/acs.inorgchem.6b01210
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Structural Versatility in an Unusual Family of anti-Perovskite Fluorides: [Cu(H2O)4]3[(MF6)(M′F6)]

Abstract: A series of six anti-perovskite fluorides of the type [Cu(H2O)4]3(M1-xM'xF6)2 (where M and M' = V, Cr, Mn, Fe as well as M = Fe and M' = V and Cr) was synthesized as high-quality single crystals via a mild hydrothermal route. These materials belong to a class of perovskite-based structures in which the anions and cations of the regular ABX3 perovskite structure have exchanged positions. Two complex anions, MF6(3-) and M'F6(3-), occupy the normal A and B cation positions, while three complex cations, [Cu(H2O)4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…[62] The observed two absorption maxima at 700 nm and 450 nm can be assigned to the expected transitions for the d 2 (V 3+ ) electron configuration; 3 T 1g (F)  3 T 2g (F) and 3 T 1g (F)  3 T 1g (P). [43] 3…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[62] The observed two absorption maxima at 700 nm and 450 nm can be assigned to the expected transitions for the d 2 (V 3+ ) electron configuration; 3 T 1g (F)  3 T 2g (F) and 3 T 1g (F)  3 T 1g (P). [43] 3…”
Section: Thermal Analysismentioning
confidence: 99%
“…This approach, while successful, yields organicinorganic hybrid products instead of pure inorganic phases. Our recent findings demonstrated that the acetate group can act as a mild reducing agent under acidic conditions and avoid being incorporated into the final product [9,43]. Adapting this approach, herein, we report a synthetic strategy to form V 3+ , in situ, under acidic, mild hydrothermal conditions, and discuss the synthesis and physical properties of the new vanadium(III) phase, NaV(HPO 4 ) 2 .…”
Section: Introductionmentioning
confidence: 97%
“…Simple molecular fluorides such as these are uncommon, as only eight of over 50 ternary (M x U y F z ) and quaternary (M w M′ x U y F z ) uranium­(IV) structures (M, M′ = NH 4 + , group 1–13 metal ions, Ge 4+ , Sn 2+/4+ , Pb 2+/4+ , Sb 3+/5+ ) currently in the Inorganic Crystal Structure Database (ICSD) feature such distinct uranium environments. The remaining structures all feature corner-, edge-, or face-sharing structures and one- to three-dimensional topologies, most of which are held together by μ 2 bridging fluorides. ,, One important exception is UF 6 , which sublimes at relatively mild temperature alongside homologue UCl 6 , due to weak van der Waals interactions between discrete octahedral molecules. , …”
Section: Introductionmentioning
confidence: 99%
“…10,11 More recently, a number of ternary and quaternary hydrated, hydronium, alkali, and transition metal uranium uorides have been reported for potential applications as phases for separation of actinides or use in molten ux reactors. [12][13][14][15][16][17][18][19][20] These studies yielded the rst high-quality structural data of rhombohedral Na 7 U 6 F 31 , as well as the rst syntheses of NaUF 5 and NaU 2 F 9 . The development of the copper-catalyzed U 6+ /U 4+ in situ reduction step by Yeon, et al 19 has led to the production of over a dozen new ternary and quaternary uranium uorides, but the remarkable stability of Na 4 CuU 6 F 30 inhibited the production of sodium uranium uorides until recently.…”
Section: Introductionmentioning
confidence: 99%